2014
DOI: 10.1371/journal.pone.0111788
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics to Delineate Pathogenic Potential in Non-O157 Shiga Toxin-Producing Escherichia coli (STEC) from Patients with and without Haemolytic Uremic Syndrome (HUS) in Norway

Abstract: Shiga toxin-producing Escherichia coli (STEC) cause infections in humans ranging from asymptomatic carriage to bloody diarrhoea and haemolytic uremic syndrome (HUS). Here we present whole genome comparison of Norwegian non-O157 STEC strains with the aim to distinguish between strains with the potential to cause HUS and less virulent strains. Whole genome sequencing and comparisons were performed across 95 non-O157 STEC strains. Twenty-three of these were classified as HUS-associated, including strains from pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 76 publications
(74 reference statements)
5
31
0
Order By: Relevance
“…Stx variants (e.g. stx2d), which have been shown to be more specific predictors of severe illness than Stx type, are not yet available in BC (13,15,16,(18)(19)(20)38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stx variants (e.g. stx2d), which have been shown to be more specific predictors of severe illness than Stx type, are not yet available in BC (13,15,16,(18)(19)(20)38).…”
Section: Discussionmentioning
confidence: 99%
“…STEC stx genes produce Shiga toxins 1 (Stx1) and 2 (Stx2). Stx2 is associated with severe illness and HUS (8,(12)(13)(14)(15)(16)(17)(18)(19)(20). Furthermore, Stx2 is associated with STEC O157, which explains this serogroup's higher pathogenicity (17,21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, phylogenetic grouping could be effective for assessing the pathogenicity of these strains further. All hemolytic uremic syndrome (HUS)-associated STEC strains (Haugum et al, 2014) and more than half of the EPEC strains (Staples et al, 2013;Wang et al, 2013) isolated from diarrhea patients are from the phylogroup B1. Phylogenetic grouping examined in this study and other surveys indicated that group A and B1 were predominant among the DEC isolates from foods, consistent with the findings reported by previous studies (Koo et al, 2012;Siriwan-Sirikaew et al, 2015;Ombarak et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Five of these had CRISPR arrays related to the CRISPR array of the “new French clone” (Yin et al, 2013 ; DEC9A, DEC9B, DEC9C, DEC9D, and DEC9E) and one isolated in France in 1952 (DEC10D) with a CRISPR array related to the reference EHEC O26:H11 strain (Hazen et al, 2012 ). Three human O26:H11 stx2a positive strains isolated in Norway (FHI4, FHI24, and FHI27) were also included (Haugum et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%